Perspective taking, empathic concern, and perceived humanness of people with dementia. Issue 9 (2nd September 2017) - Miron, Anca M.; McFadden, Susan H.; Nazario, Amanda S.; Buelow, Jennifer
ABSTRACT: Past work has documented the detrimental psychological and health outcomes of negative age stereotypes and dehumanization of older adults. We investigated the role of perspective taking in enhancing positive perceptions of humanness of older individuals with dementia. To manipulate perspective taking, participants either imagined the situation of an older woman with dementia ( n  = 35), remained objective and detached ( n  = 37), or received no instructions ( n  = 35). We measured evidence of impairments of humanness needed to conclude personhood loss for the woman with dementia (i.e., humanness standards). Compared to stay-objective participants, imagine-other and no-instructions participants asked for more evidence of impairments of uniquely human characteristics, but not of human nature characteristics, in order to conclude personhood loss for the woman with dementia. Empathic concern for the woman with dementia mediated this effect. We discuss the importance of studying perceptions of personhood of those with dementia with a focus on the person with dementia and his or her social and personal connections with others. Strategies for developing and maintaining healthy relationships with persons with dementia based on active perspective taking are also discussed.